Praktik Upah Buruh Bangunan Ditinjau dari Perspektif Hukum Ekonomi Syari’ah (Studi Kasus di Pondok Pesantren Jari Nabi): Penelitian - Rusdi Zaini Fajri; Zaenal Abidin; Kurniawan; Wargo; Dini Ayu Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Wages in Arabic are often referred to as ajrun/ajran which means giving a gift/wages. The word ajran has two meanings, namely recompense or work and reward. While wages according to the term are money and so on that are paid as a reward for services or payment for the energy that has been devoted to doing something. The purpose of the study was to determine the wage system for construction workers at the Jari Nabi Islamic Boarding School, as well as the views of Islamic law on wages for construction workers at the Jari Nabi Islamic Boarding School with a qualitative approach from The results of this study explain the practice of the wage system that occurs at the Jari Nabi Islamic Boarding School, divided into 2 parts, there are daily workers whose wages are calculated per day and paid per week by the institution. The institution provides wages according to the agreement.